The Impact of Technological and Socio-Economic Factors on Personnel Security Elements of the Region - Olga S. Nadezhina; Ekaterina A. Avduevskaya; Elizaveta A. Kulchitskaya (Регионология)
Introduction. In conditions of instability, regions face the problems of population outflow, declining quality of labor resources, and growing imbalance in the labor markets. The solution of these systemic problems is of strategic importance for maintaining human resources and national security as a whole. The development of effective mechanisms to ensure personnel security of the region is impossible without an objective assessment of its internal reserves on the basis of economic and mathematical modeling. Due to the relative novelty of the category “personnel security of the region” in the domestic scientific literature there are no studies on the data of the subjects of the Russian Federation on the relationship between the indicators of technological and socio-economic development with the indicators of personnel security, which limits the possibility of developing sound recommendations for the management of regional systems in the context of modern personnel and demographic challenges. The purpose of the article is to assess the impact of socio-economic and technological factors on the elements of personnel security of the region.